Endothelial anthrax toxin receptor 2 plays a protective role in liver fibrosis - Xiaojuan Huang; Liyin Zhang; Wei Luo; Yu Zeng; Xiaoxue Li; Nan Yang; Wenwen Huang; Bi-Sen Ding (Frontiers in Cell and Developmental Biology, 2024)
Hepatocellular carcinoma is one of the leading cancers worldwide and is a potential consequence of fibrosis. Therefore, the identification of key cellular and molecular mechanisms involved in liver fibrosis is an important goal for the development of new strategies to control liver-related diseases. Here, single-cell RNA sequencing data (GSE136103 and GES181483) of clinical liver non-parenchymal cells were analyzed to identify cellular and molecular mechanisms of liver fibrosis. The proportion of endothelial subpopulations in cirrhotic livers was significantly higher than that in healthy livers. Gene ontology and gene set enrichment analysis of differentially expressed genes in the endothelial subgroups revealed that extracellular matrix (ECM)-related pathways were significantly enriched. Since anthrax toxin receptor 2 (ANTXR2) interacts with the ECM, the expression of ANTXR2 in the liver endothelium was analyzed. ANTXR2 expression in the liver endothelium of wild-type (WT) mice significantly decreased after a 4-time sequential injection of carbon tetrachloride (CCl4) to induce liver fibrosis. Next, conditional knockout mice selectively lacking Antxr2 in endothelial cells were generated. After endothelial-specific Antxr2 knockout mice were subjected to the CCl4 model, the degree of liver fibrosis in the knockout group was significantly more severe than that in the control group. In addition, ANTXR2 in human umbilical vein endothelial cells promoted matrix metalloproteinase 2 (MMP2) activation to degrade the ECM in vitro. Finally, endothelial-specific overexpression of Antxr2 alleviated the development of liver fibrosis following adeno-associated virus treatment. Collectively, these results suggested that endothelial ANTXR2 plays a protective role in liver fibrosis. This function of ANTXR2 may be achieved by promoting MMP2 activation to degrade the ECM.